Implications of empathize in the design thinking method on the value of entrepreneurship creativity (study on SMES in Depok City) - Uswatun Hasanah; Azizah Fauziyah; Ismail Yusuf (Institute of Computer Science (IOCS), 2023)
Entrepreneurship is simply associated with activity creating a business that has potential to financial benefits. Many of the business actors in Depok City set up businesses solely because want to gain financial benefits and don’t understand the basic values of entrepreneurship, therefore this research aims to determine the impact of empathize method approach on entrepreneurial creativity value of entrepreneur participants in Depok City in 2020. This a quantitative research use descriptive approach, and a quasi-experimental method. Population in this study taken from New Entrepreneurial Participants in City of Depok for the 2020 Fiscal Year. Saturated sample of 75 participants used in this research. Based on the output, can be concluded that there are differences in creativity after using the empathy map approach. The results can contribute to the field of educational Entrepreneurship, related to the treatment given, namely the empathy approach, which can have an impact on entrepreneurial creativity. The Department of Cooperatives and Micro Enterprises for the City of Depok can focus their training by adding an empathetic approach or design thinking method to the participants to encourage them to see opportunities in a targeted and creative way in entrepreneurship so can improve their entrepreneurial skills and overcome unemployment.